Green-solvent-processed formamidinium-based perovskite solar cells with uniform grain growth and strengthened interfacial contact via a nanostructured tin oxide layer. Issue 1 (1st November 2022) - Wu, Xueyun; Zheng, Yiting; Liang, Jianghu; Zhang, Zhanfei; Tian, Congcong; Zhang, Zhiang; Hu, Yixuan; Sun, Anxin; Wang, Chenyang; Wang, Jianli; Huang, Ying; Zhang, Zhifu; et al.
Abstract : This work demonstrates a green-solvent-processed FA-based perovskite film based on a SnO2 -NR substrate with Cl-terminated bifunctional supramolecule passivation and has achieved a highest PCE of 22.42% with long-term stability. Abstract : Green-solvent-processed perovskite solar cells (PSCs) have reached an efficiency of 20%, showing great promise in safe industrial production. However, the nucleation process in green-solvent-based deposition is rarely optimized, resulting in randomized crystallization and much lowered reported efficiencies. Herein, a nanostructured tin oxide nanorods (SnO2 -NRs) substrate is utilized to prepare a high-quality formamidinium (FA)-based perovskite film processed from a green solvent of triethyl phosphate (TEP) with a low toxic antisolvent of dibutyl ether (DEE). Compared with SnO2 nanoparticles, the oriented SnO2 -NRs can accelerate the formation of heterogeneous nucleation sites and retard the crystal growth process of the perovskite film, resulting in a high-quality perovskite film with uniform grain growth. Furthermore, a chlorine-terminated bifunctional supramolecule (Cl-BSM) is introduced to passivate the increasing interfacial defects due to the vast contact area in SnO2 -NRs. Correspondingly, the substrate design of SnO2 -NRs with Cl-BSM increases the power conversion efficiency (PCE) of green-solvent-processed PSCs to 22.42% with an open-circuit voltage improvement from 1.02 to 1.12 V, which can be attributed to the uniform grain growth and reduced carrier recombination at the SnO2 -NRs/perovskite interface. More importantly, the photo and humidity stabilities of the unencapsulated device for up to 500 and 1000 hours are also achieved with negligible interfacial delamination after aging. This work provides a new perspective on the future industrial scale production of PSCs using environment-friendly solvents with compatible substrate design.